Case report: A young man with non-rapid eye movement parasomnias in a KCNT1-related epilepsy family - Sheng, Dandan; Lv, Yefan; Li, Xinru; Liu, Jing; Liu, Weiping (Frontiers in Neurology, 2023)
Differentiating between nonrapid eye movement (NREM) parasomnias and sleep-related hypermotor epilepsy (SHE) is challenging, as they exhibit similar episodes during sleep. A relatively high prevalence of NREM parasomnias had been detected in families with SHE. However, the common pathophysiologic mechanism is not clear completely. There have been no previous reports of KCNT1-related SHE combined with NREM parasomnias. In this report, we described a 17-year-old male from a KCNT1 mutation family who exhibit ed complex abnormal behaviors during sleep , which have been confirmed as epileptic seizures combined with NREM parasomnias through video-electroencephalogram (vEEG) and video-polysomnography (vPSG). The present article provides a reasoning process to evaluate unusual nocturnal behaviors. Furthermore, our analysis suggests a new potential association between NREM parasomnias and KCNT1 mutations.